18F-FDG PET/CT revealed small bowel metastasis from large cell lung carcinoma after treatment improvement: a case report - Jiang, Maoyan; Li, Shun; Wen, Shuncui; Hu, Xianwen (Frontiers in Medicine, 2025)
Large cell lung carcinoma (LCLC) is a highly aggressive form of non-small cell lung cancer that frequently metastasizes to the brain, liver, bone, adrenal gland, and lymph nodes. Gastrointestinal metastasis, particularly to the small bowel, is relatively uncommon. Herein, we present a case of a patient with LCLC who developed abdominal pain 3 years after initial treatment response. Abdominal computed tomography (CT) and fluorine-18 fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/CT imaging revealed a small bowel lesion, which was subsequently confirmed as metastatic disease from LCLC via pathological examination. As with our case highlights that, although small bowel metastases are rare in LCLC, they should be considered as a differential diagnosis in patients with LCLC who present gastrointestinal symptoms such as abdominal pain, bloating, or hematochezia following treatment.